2017
DOI: 10.1063/1.4981218
|View full text |Cite
|
Sign up to set email alerts
|

High-power tunable laser driven THz generation in corrugated plasma waveguides

Abstract: The excitation of THz radiation by the interaction of an ultra short laser pulse with the modes of a miniature corrugated plasma waveguide is considered. The axially corrugated waveguide supports the electromagnetic (EM) modes with appropriate polarization and subluminal phase velocities that can be phase matched to the ponderomotive potential associated with laser pulse, making significant THz generation possible. This process is studied via full format Particle-in-Cell (PIC) simulations that, for the first t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…2 (left). If the plasma density in such a narrow well is modulated in the longitudinal direction due to, for example, the modulation instability, sub-luminal beam-driven modes can resonate with slow waveguide electromagnetic modes [5]. Then, these waveguide modes escape from the local density wells in the predominantly longitudinal direction via regular longitudinal inhomogeneity of plasma density on the scale of the magnetic field corrugation (10 cm).…”
Section: Short Analysis Of Measurement Resultsmentioning
confidence: 99%
“…2 (left). If the plasma density in such a narrow well is modulated in the longitudinal direction due to, for example, the modulation instability, sub-luminal beam-driven modes can resonate with slow waveguide electromagnetic modes [5]. Then, these waveguide modes escape from the local density wells in the predominantly longitudinal direction via regular longitudinal inhomogeneity of plasma density on the scale of the magnetic field corrugation (10 cm).…”
Section: Short Analysis Of Measurement Resultsmentioning
confidence: 99%
“…It has been reported that THz energy of more than 5 µJ is generated through this mechanism (Kim et al 2008). THz radiation has also been generated by laser pulses propagating in short corrugated plasma channels (Antonsen et al 2007;Pearson et al 2011;Miao et al 2017). It is found that a pulse energy of 0.5 J generates a terahertz energy of 6 mJ through the corrugated plasma channel (Pearson et al 2011).…”
Section: Introductionmentioning
confidence: 96%
“…In type II and III solar radio bursts (Henri et al 2019;Yao et al 2021), emissions at the plasma frequency ω p and its second harmonic are often comparable in intensities, although the escape of ω p -radiation from the generation region should be significantly complicated by the proximity to the cutoff frequency of EM waves. Recently, the processes of transformation of electrostatic plasma oscillations into EM ones near the cutoff frequency have been actively discussed with regard to generation of powerful terahertz pulses (Hur et al 2017;Miao, Palastro & Antonsen 2017;Kwon et al 2018;Volchok, Timofeev & Annenkov 2019;Kalmykov, Elle & Schmitt-Sody 2020). A similar problem of generating narrowband THz radiation of a multimegawatt power level is being solved today in laboratory beam-plasma experiments (Arzhannikov et al 2014(Arzhannikov et al , 2016 in order to create a powerful radiation source that can be used in fundamental science (Dhillon et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the processes of transformation of electrostatic plasma oscillations into EM ones near the cutoff frequency have been actively discussed with regard to generation of powerful terahertz pulses (Hur et al. 2017; Miao, Palastro & Antonsen 2017; Kwon et al. 2018; Volchok, Timofeev & Annenkov 2019; Kalmykov, Elle & Schmitt-Sody 2020).…”
Section: Introductionmentioning
confidence: 99%